GE_GERICHTE A/2442/2024 vom 16. April 2025 - GE Cour de justice (2025)
MÉNAGE COMMUN;AUTORISATION DE SÉJOUR;VIE SÉPARÉE | LEI.42.al1; LEI.50.al1.leta; LEI.50.al1.letb; LEI.30.al1.letb; OASA.31; LEI.64.al1.letc